Psihološki korelati učenja učenja: študije metakognicije in samoregulacije : razvoj in možne praktične aplikacije - Bakračevič Vukman, Karin (2010)
Psychological Correlates of Learning Learning: studies of metacognition and self-regulation: development and possible practical applications. No abstract.